2019
DOI: 10.1176/appi.ajp.2019.18040380
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Network-Based Cortical Thickness Reductions in Schizophrenia

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 64 publications
11
101
1
4
Order By: Relevance
“…Our control analyses on a subset of patients indicate that the network effects reported here are unlikely to be correlated with chlorpromazine equivalent antipsychotic medication dose. Other groups have recently reported similar relationships between anatomical covariance networks and changes in cortical thickness in firstepisode psychosis, chronic schizophrenia and treatmentresistant schizophrenia [73], suggesting that the observed effect is likely to be present earlier in the disease and in drug-naive patients. The authors thank Dr. Alessandra Griffa for data collection and processing of healthy structural and functional networks and providing insightful comments on the manuscript.…”
Section: Methodological Considerationsmentioning
confidence: 60%
See 2 more Smart Citations
“…Our control analyses on a subset of patients indicate that the network effects reported here are unlikely to be correlated with chlorpromazine equivalent antipsychotic medication dose. Other groups have recently reported similar relationships between anatomical covariance networks and changes in cortical thickness in firstepisode psychosis, chronic schizophrenia and treatmentresistant schizophrenia [73], suggesting that the observed effect is likely to be present earlier in the disease and in drug-naive patients. The authors thank Dr. Alessandra Griffa for data collection and processing of healthy structural and functional networks and providing insightful comments on the manuscript.…”
Section: Methodological Considerationsmentioning
confidence: 60%
“…Interestingly, several recent studies found complementary results. Wannan and colleagues found that cortical thinning in schizophrenia was more likely among areas with greater anatomical covariance [73]. Di Biase and colleagues found that cortical thinning and reduction in local white matter anisotropy are anticorrelated in patients with schizophrenia [23].…”
Section: Network Patterning Of Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is associated with profound changes in brain structure, including altered cortical morphology (1)(2)(3)(4), subcortical volume loss (5) and white matter alterations (6)(7)(8)(9) leading to structural connectopathies (10)(11)(12)(13)(14)(15). Despite numerous cross-sectional and longitudinal investigations, the heterogeneity of schizophrenia has defied attempts to derive reproducible and definitive brain maps of the precise anatomical loci of these structural changes.…”
Section: Introductionmentioning
confidence: 99%
“…20 It is important to further our understanding of the possible neurobiological mechanisms the underlie MR-visible cortical morphology as alterations in cortical thickness could act as a potential phenotypic marker of several common neurodevelopmental and psychiatric disorders including autism spectrum disorders and schizophrenia. [21][22][23][24] One promising approach to this problem pairs non-invasive MRI with genetic databases that detail the transcription of thousands of genes across the brain at high spatial resolution. This allows a precise comparison between patterns of gene expression and in vivo neuroanatomy.…”
Section: Introductionmentioning
confidence: 99%